A Study on Awareness and Practice Regarding Vitamin A Intake and Its Deficiency Disorders Among Mothers of Pre-School Children in Khirasara Village, Rajkot, Gujarat - Ankit M Sheth; Matib M Rangoonwala; Kaushik K Lodhiya; Dipesh D Zalavadiya; Nirav B Joshi (Medsci Publications, 2016)
Introduction: Vitamin A deficiency (VAD) is one of the most im- portant causes of preventable childhood blindness and is a major contributor to morbidity and mortality from infections. The present study was conducted among mothers of pre-school child- ren to study awareness and practice regarding vitamin A intake and their deficiency disorders. Methods: It was a cross sectional study conducted in Khirasara village of Rajkot district from January to April 2015. Out of total 196 mothers of pre-school children in the village, 98 (50% of the total after convenient sampling) were selected. Ninety five moth- ers consented and gave complete response. Interview was con- ducted using a pretested semi structured questionnaire. Results: Mean age was 25.9 years, 38.9% were illiterate and 80% were non-working. 32.6% knew about vitamin A rich foodstuffs. 18.9% were aware about vitamin A prophylaxis programme. 27.4% included vitamin A rich foods in diet of their children.  68.0% didn't know about any symptoms about vitamin A deficiency dis- orders. Conclusion: Significant low levels of knowledge and practice re- garding vitamin A intake was found in illiterate mothers. Multi- para and literate mothers were significantly more aware about vi- tamin A prophylaxis programme.